Mia Mayhem and the wild garden - West, Kara (West, Kara. Mia Mayhem, 2023)
As part of her new mega-botany class at the Program for In-Training Superheroes, Mia Mayhem has to grow a plant from superseeds all on her own, but when her plant grows out of her control, she must find a way to stop the ensuing chaos.